EMDR AS A WAY TO CORRECT THE ACTUAL MENTAL STATES OF STUDENTS DURING THE EXAMINATION SESSION - Gavrilova, Victoria; Ivashko, Svetlana (Modern Psychology, 2023)
The article presents the results of a study of the application of the method of desensitization and processing by eye movement and its effect on the unfavorable mental states of students during the examination session.The purpose of the study: to identify the possibilities of changing the actual conditions of students using the method of desensitization and processing by eye movement.The following tasks are highlighted : 1) to conduct a theoretical and bibliographic analysis of literary sources devoted to the problem of actual mental states; 2) to determine the actual mental states of students during the examination session; 3) to identify the effectiveness of the method of desensitization and processing by eye movement in the regulation of unfavorable mental states of students.As a result of the conducted research, we made the following conclusions: DPDG is a fast and effective method that in a short period of time allowed to reduce the intensity of such emotions and feelings as fear, anger, tension and anxiety. The effect of using the method of desensitization and processing by eye movement allowed to increase the level of vitality, efficiency, improve well-being, reduce the impact of stress, reduce the level of tension, get out of a state of fatigue and satiety, as evidenced by the obtained data of primary and secondary testing.
Keywords: current mental states; stress; tension; regulation; examination session; students; EMDR